2019
DOI: 10.1126/scitranslmed.aav5685
|View full text |Cite
|
Sign up to set email alerts
|

Multispecific anti-HIV duoCAR-T cells display broad in vitro antiviral activity and potent in vivo elimination of HIV-infected cells in a humanized mouse model

Abstract: Adoptive immunotherapy using chimeric antigen receptor–modified T cells (CAR-T) has made substantial contributions to the treatment of certain B cell malignancies. Such treatment modalities could potentially obviate the need for long-term antiretroviral drug therapy in HIV/AIDS. Here, we report the development of HIV-1–based lentiviral vectors that encode CARs targeting multiple highly conserved sites on the HIV-1 envelope glycoprotein using a two-molecule CAR architecture, termed duoCAR. We show that transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 57 publications
1
131
0
Order By: Relevance
“…Furthermore, chimeric antigen receptor (CAR)-T cells, with the extracellular domain from the singlechain variable fragment of bNAb, can effectively kill reactivated HIV-1-infected CD4 + T cells [86]. Multispecific anti-HIV duoCAR-T cells display potent elimination of HIV-infected cells and mitigate CD4 + T cell loss in a humanized mouse model of intrasplenic HIV infection [87]. A newly designed convertibleCAR-T cell system capable of binding to a variety of bNAbs yields greater breadth and control, representing a potential strategy for targeting the latent HIV-1 reservoir [88].…”
Section: Affecting the Hiv-1 Reservoirmentioning
confidence: 99%
“…Furthermore, chimeric antigen receptor (CAR)-T cells, with the extracellular domain from the singlechain variable fragment of bNAb, can effectively kill reactivated HIV-1-infected CD4 + T cells [86]. Multispecific anti-HIV duoCAR-T cells display potent elimination of HIV-infected cells and mitigate CD4 + T cell loss in a humanized mouse model of intrasplenic HIV infection [87]. A newly designed convertibleCAR-T cell system capable of binding to a variety of bNAbs yields greater breadth and control, representing a potential strategy for targeting the latent HIV-1 reservoir [88].…”
Section: Affecting the Hiv-1 Reservoirmentioning
confidence: 99%
“…Additionally, it was observed that CAR T cells persisted at high levels for at least 6 months in the cerebrospinal fluid (CSF) (106), a compartment that contains a significant but hard-to-reach reservoir of HIV (107). A recent study showed that primary T cells transduced with a multispecific CAR (targeting both the gp120 CD4-binding site and the gp120 co-receptor-binding site) had the ability to potently reduce cellular HIV infection by up to 99% in vitro and >97% in vivo (108).…”
Section: Car T Therapy For Hiv Curementioning
confidence: 99%
“…These studies are now re-emerging as the improvements in CAR design done for cancer are being translated and adapted to fight HIV infection [reviewed by (217)]. Recently, multispecific anti-HIV CAR T cells targeting different portions of the HIV envelope protein were shown to control HIV infection in a humanized mouse model (218). iPSCderived NK cells, unmodified or carrying HIV-targeted chimeric receptor, were also developed and were shown to suppress HIV replication and CD4+ T cell infection in vitro and in vivo (219,220).…”
Section: Direct Cell Reprogramming For Immunotherapy: Future Applicatmentioning
confidence: 99%